Antioxidative and chelating activities of phenylpropanoid glycosides from Pedicularis striata - Li Ji; Ge Rui-Chang; Zheng Rong-Liang; Liu Zi-Min; Jia Zhong-Jian (Acta Pharmacologica Sinica, 2016)
AIM: To study the antioxidative and iron chelating activities of phenylpropanoid glycosides (PPG) isolated from a Chinese herb Pedicularis striata. METHODS: Antioxidative effects of PPG on lipid peroxidation induced by FeSO4-edetic acid in linoleic acid were measured by thiobarbituric acid method. Chelating activities of PPG for Fe2+ were tested by differential spectrum method. RESULTS: The reaction rates (A532.min-1) of lipid peroxidation were 0.0046 in the control, 0.0021 in verbascoside group, and 0.0008 in isoverbascoside group. The chelating activity of isoverbascoside was 2-fold stronger than that of verbascoside. Permethyl verbascoside showed neither antioxidative nor chelating activities. CONCLUSION: The inhibitory effects of PPG with phenolic hydroxy groups on lipid peroxidation are owing to their chelating properties. Under physiological condition PPG-Fe2+ chelates are sufficiently stable. Thus PPG are able to inhibit the Fe(2+)-dependent lipid peroxidation in vivo through chelating Fe2+ and exhibit their therapeutic potential by the same mechanism in vitro.